Attitude and Knowledge Relationship with Sexual Behavior at Risk of Sexually Transmitted Infection (STI) in Male Adolescents in Indonesia (IDHS Data Analysis 2017) - Nur Asiah; Agnes Yohana Sondi; Nining Parlina; Della Raymena Jovanka (Indonesian Journal of Medical Sciences and Public Health, 2021)
Introduction: Indonesia Population Demographic Survey in 2017 recorded that 8% of teenage boys and 2% of teenage girls admitted to having sexual intercourse. This certainly worries all of us who hope today's youth will be a demographic bonus. Sexual behavior is at risk of impacting the issue of Unwanted Pregnancy (KTD), abortion, Sexually Transmitted Infections (STIs), and the ongoing incidence of HIV and AIDS. Objective: to confirm the relationship of attitudes and knowledge with risky sexual behavior in adolescent boys in Indonesia. Methods: This type of research is quantitative analytics using a cross-sectional design and sourced from secondary data of the Indonesian Health Demographic Survey 2017. The population in this study was 13,079 adolescent men aged 15-24, sampling 10,710 with saturated sampling techniques. Bivariate data analysis using the chi-square test (0.05). Results: were obtained by adolescents with a positive attitude of 52.1%, knowledgeable 77.8%, and 13.1% risky sexual behavior. Test results showed there was an attitude relationship with risky sexual behavior with p-value = 0.000 and there was a knowledge relationship with risky sexual behavior with p-value = 0.000. Conclusions: This study are expected to be used as input for the creation of risky sexual behavior prevention programs in adolescents and form the basis for the creation of an educational model related to adolescent reproductive health for parents and educational institutions.